Library Information System Using QR Code Technology at Patra Mandiri 2 Junior High School, Palembang - Rey Aprinaldo (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2025)
The library of Patra Mandiri 2 Junior High School in Palembang still employs manual data collection methods, where records such as book inventories and transactions are maintained using notebooks and paper-based systems. This approach is time-consuming and prone to human error, which negatively affects library management and service efficiency. To overcome these limitations, a computerized Library Information System (LIS) was developed by integrating QR Code (Quick Response Code) technology as the central component for data access and management. The QR Code serves as a primary key for retrieving book information, while a webcam functions as the QR Code scanner. The research was conducted at Patra Mandiri 2 Junior High School, located in the Pertamina Complex, Flamboyan Street, Sungai Gerong, Plaju District, Banyuasin Regency, South Sumatra 30763. The study applied a descriptive research method and utilized the Rapid Application Development (RAD) model for system development. The objective of this study is to build a web-based library information system that integrates QR Code technology to facilitate borrowing, returning, and reporting processes. The resulting system enables efficient, accurate, and accessible library operations for students and staff.